Sulfur Dioxide Removal by Using Leather Factory Wastewater - Ipek, Ubeyde (Wiley, 2010)
This study shows the ability of wastewater from a liming and unhairing unit in a leather factory to remove sulfur dioxide (SO2). The pH of the wastewater reached neutral values during SO2 removal by wet scrubbing. Experiments were carried out at five inlet flue SO2 concentrations. These concentrations were 1000, 2000, 3000, 4000, and 5000 ppm. The results indicate that the inlet SO2 concentration influenced the removal efficiency and the maximum removal efficiencies varied from 96 to 99%. When the inlet SO2 concentration and the flow rate of the flue were kept around 1000 ppm and 44 L/s, respectively, the SO2 concentration in the outlet flue was determined to be less than 50 ppm after 80 s. Subsequently, the SO2 Concentration ranged from 10 - 50 ppm after 13 minutes. At the end of the running period, the wastewater was also neutralized. When the inlet concentration was increased to around 2000 ppm, the concentrations of SO2 in the outlet flue ranged from 10 - 50 ppm after 7 minutes. SO2 rernoval decreased as the SO2 concentration in the inlet flue increased.
Keywords: Leather factory wastewater; Liming; Neutralization; Sulfur dioxide removal; Unhairing